2009
DOI: 10.1074/jbc.m109.056838
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Inhibits Insulin-like Growth Factor-I Induction of Chondrocyte Proteoglycan Synthesis through Differential Regulation of Phosphatidylinositol 3-Kinase-Akt and MEK-ERK MAPK Signaling Pathways

Abstract: The ability of insulin-like growth factor I (IGF-I) to stimulate cartilage matrix synthesis is reduced in aged and osteoarthritic cartilage. Aging and osteoarthritis are associated with an increase in reactive oxygen species, which we hypothesized would interfere with normal IGF-I signaling. We compared IGF-I signaling in normal and osteoarthritic human articular chondrocytes and investi-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
164
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 159 publications
(177 citation statements)
references
References 63 publications
13
164
0
Order By: Relevance
“…We also analyzed the extent by which the candidate treatment with the rAAV-human IGF-I (rAAV-hIGF-I) vector was capable of durably restoring the structure of human OA cartilage vis-à-vis normal cartilage. Finally, we investigated the influence of rAAV-mediated IGF-I production upon the expression of key effectors of the IGF-I axis, specifically the IGF-binding proteins 3, 4 and 5 (IGFBP-3 to IGFBP-5) as well as the IGF-I receptor (IGF-IR) and downstream mitogenactivated protein kinase/extracellular signal-regulated kinase 1/2 (MAPK/ERK-1/2) and phosphatidylinisitol-3/Akt (PI3K/Akt) signal transduction pathways (33)(34)(35)(36)(37)(38)(39), reported as being inhibitors (IGFBP3 and IGFBP4) (40)(41)(42) or potentiators (IGFBP5 and IGF-IR) (42,43) of the IGF-I actions during OA pathogenesis.…”
Section: Benefits Of Recombinant Adeno-associated Virus (Raav)-mediatmentioning
confidence: 99%
“…We also analyzed the extent by which the candidate treatment with the rAAV-human IGF-I (rAAV-hIGF-I) vector was capable of durably restoring the structure of human OA cartilage vis-à-vis normal cartilage. Finally, we investigated the influence of rAAV-mediated IGF-I production upon the expression of key effectors of the IGF-I axis, specifically the IGF-binding proteins 3, 4 and 5 (IGFBP-3 to IGFBP-5) as well as the IGF-I receptor (IGF-IR) and downstream mitogenactivated protein kinase/extracellular signal-regulated kinase 1/2 (MAPK/ERK-1/2) and phosphatidylinisitol-3/Akt (PI3K/Akt) signal transduction pathways (33)(34)(35)(36)(37)(38)(39), reported as being inhibitors (IGFBP3 and IGFBP4) (40)(41)(42) or potentiators (IGFBP5 and IGF-IR) (42,43) of the IGF-I actions during OA pathogenesis.…”
Section: Benefits Of Recombinant Adeno-associated Virus (Raav)-mediatmentioning
confidence: 99%
“…Disrupted pro-anabolic IGF-1 signaling has been implicated in the pathogenesis of OA, and age-associated reductions in the chondrocyte response to IGF-1 have been associated with oxidative stress (26,27). The aim of this study was to examine whether menadione-induced oxidative stress could promote chondrocyte PRX hyperoxidation in an age-related manner and determine whether this was associated with disrupted IGF-1 signaling, chondrocyte cell death, and osteoarthritis.…”
mentioning
confidence: 99%
“…We chose to focus on the redox regulation of the chondrocyte insulin-like growth factor-1 (IGF-1) signaling pathway because of previous studies demonstrating that IGF-1 promotes cartilage matrix synthesis and chondrocyte survival while reducing chondrocyte catabolic activity (25,26). Disrupted pro-anabolic IGF-1 signaling has been implicated in the pathogenesis of OA, and age-associated reductions in the chondrocyte response to IGF-1 have been associated with oxidative stress (26,27).…”
mentioning
confidence: 99%
“…ROS could decrease the collagen and protein synthesis through suppressing the mitochondrial oxidative phosphorylation and adenosine triphosphate (ATP) formation (Johnson et al, 2000). It was suggested that insulin-like growth factor-1 (IGF-1) might be the promoter of the matrix formation, but there were evidences indicating that ROS contributed to the chondrocyte IGF-1 resistance and reduced the proteoglycan synthesis by causing an imbalance in the activity between the phosphatidylinositol 3-kinase-Akt pathway and the MEK-ERK MAPK signaling pathway (Yin et al, 2009). The decomposition was more than the synthesis, which speedups the progression of matrix degradation.…”
Section: Oa and Rosmentioning
confidence: 99%